Android application for Singapore tourism - Huang, Wenjie (2017)
The “Smartphone” is a widely used technological device with billions of users worldwide. Current smartphones have much more functions rather than just simply making phone calls and sending text messages. These newer functions are advance operating system, high milliamp hour (mAH) battery, extended Random-access memory (RAM), fingerprint scanner, advance sensors, screen mirroring, wireless print and many more. This changes the way people live in the 21st century. This project specifically aims to explore the area in which smartphone can be used as a platform to provide a comprehensive guide for all tourists visiting Singapore. The application provides a reliable one-stop service which covers general direction guide, nearby places of interest, weather forecast, currency converter, image and text recognition, itinerary planner and car rental services. It aims to guide tourists in planning their trip to Singapore with ease as well as to achieve a new user experience using Augmented Reality (AR).